An Interdisciplinary Approach to Community-Based Service Learning; The Program Framework - Oracion, Enrique G. (Silliman Journal, 2022)
Service-learning is not designed to be a substitute for classroom teaching but to reinforce the latter by providing practical meanings to the theoretical knowledge acquired by students. As a teaching-learning strategy, it pursues the growth of students' intellectual capacity along their chosen career paths and aims to promote their sense of social responsibility by providing them the opportunity to serve the community. But the need for a holistic approach to community problems makes it imperative for the different academic units to pool resources—human, technical, and material—and to work together in the same community as co-equals. The interdisciplinary framework of the service-learning program of Silliman University guided the design and implementation of the community projects of the participating academic units. Within this framework, students and faculty coordinators involved in the service-learning program served the same community but individually addressed specific problem areas according to their expertise in a coordinated manner.